Precarious whiteness in pandemic times in China. Issue 3 (12th September 2022) - Lan, Shanshan; Sier, Willy; Camenisch, Aldina
Abstract: In this introduction we explore how the effects of the outbreak of Covid-19 in January 2020 have challenged, undermined, and transformed the racialized privileges of various groups of white migrants in China. While whiteness can be an invisible hegemonic construction in Western societies, it becomes a highly visible minority status in China. We introduce the concept of "precarious whiteness" to flesh out the multi-layered tensions in the transnational circulation and reconfiguration of white privilege, particularly in China. The articles in this special issue focus on white migrants in four domains: transnational business and entrepreneurship, Chinese-foreign families, digital media platforms, and online English teaching. Together they foreground the highly contested and fragmented nature of white racial formation in a critical historical moment of Covid-19.